Body mass index as the main predictor for length of stay in COVID-19 patients with mild and moderate symptoms: a cross-sectional study in COVID-19 emergency hospital in Indonesia - Nadhiroh, Siti Rahayu; Fitria, Anisa Lailatul; Hasugian, Armedy Ronny; Triyono, Erwin Astha; Nugroho, Nono Tri; Sinatrya, Alfadhila Khairil; Majid, Hazreen B Abdul (Universitas Airlangga, 2024)
Introduction: COVID-19 emerged as a novel global health crisis. While it has since been downgraded from its status as a public health emergency of international concern, the virus persists as a global health challenge. This study was aimed to analyze the predictors of LoS in COVID-19 patients based on nutritional status and patient characteristics data. Methods: Participants of this study were the COVID-19 patients with mild to moderate symptoms who registered in COVID-19 Emergency Hospital, East Java, Indonesia. This study involved 2850 patients extracted from medical records for further analysis. Body mass index (BMI) was generated following the standard formula measured on the first day of hospitalization. LoS was determined by the number of days of hospitalization. The Chi-square automatic interaction detection (CHAID) algorithm was employed for model building. Results: Most participants were overweight (34.6%) and obese (17.2%). Only a few participants were hospitalized with comorbidities such as hypertension (11.6%) and diabetes mellitus (4.1%). The predictive model of LoS indicated that BMI was the main predictor of COVID-19 LoS, with higher BMI showed to prolong the LoS of mild to moderate symptoms patients. Other than BMI, gender and symptoms were also indicated as COVID-19 LoS predictors. Conclusions: Nutritional status is one of the predictors of LoS in COVID-19 patients. Having higher BMI tends to prolong the LoS, especially in male and having fever. LOS was also seen among those with lower BMI less than 18.5, in patients who had cold and flu.